Total grain size distribution and morphology characteristics of the Askja 1875 C tephra - Alma Gytha Huntingdon-Williams 1992- (2018)
Recent explosive eruptions, such as the 2010 Eyjafjallajökull eruption, have highlighted the need for a larger, more detailed, global dataset of volcanic parameters, especially including total grain size distribution (TGSD). TGSD is a critical input parameter for many volcanic ash dispersal and transport models and crucial for volcanic hazard assessments. The 1875 Askja eruption was rhyolitic in composition, and one of the largest explosive historical eruptions in Iceland. It consisted of three main phases: the subplinian unit B, the phreatoplinian unit C, and the Plinian unit D. This study focuses on unit C. Grain size distribution of individual samples from Askja 1875 C were determined by sieving -6.0 to 4.0 ϕ (64 mm to 63 µm). Two methods were used to analyze the fine ash fraction. Firstly, a MassSizer was used to analyze the fraction finer than 0.5 mm (1ϕ) and secondly, a SedigraphIII was used to analyze the fraction finer than 125 µm (3 ϕ). The TGSD was reconstructed using the Voronoi Tessellation technique. The reconstructed TGSD is unimodal, with the mode at 3.5 ϕ (88 µm), median diameter of 3.6 ϕ (80 µm) and poorly sorted (σϕ = 4). Morphology analysis, by using SEM, of grain sizes 1.0 and 3.0 ϕ (0.5 mm and 125 µm) show that most of the tephra was fragmented in the ductile mode with elongated and spongy grains dominating in all the samples. Sprengigos sem hafa átt sér stað á síðastliðnum árum, t.d. gosið í Eyjafjallajökli 2010, hafa sýnt fram á þörfina fyrir betrumbættu gagnasafni eldgosa og einkennum þeirra, einkum hvað varðar heildarkornastærðar dreifingu. Heildarkornastærðar dreifing er notuð í ýmiss áháttulíkön hvað varðar eldfjallavá. Rhýolíska gosið í Öskju, 1875, er í hóp stærstu sprengigosum sem hafa átt sér stað á sögulegum tíma á Íslandi. Gosið samanstóð af þremur aðal fösum: subplínískur fasi B, pheatroplínískur fasi C og plíníski fasinn D. Í þessari rannsókn er verið að skoða C fasa, sem einkennist af fínum massa, sem ferðaðist alla leið til Skandinavíu. Hand sigtun var notuð til að finna ...